2000
DOI: 10.1007/bf02987348
|View full text |Cite
|
Sign up to set email alerts
|

Ecological recovery of vegetation at a former industrial sludge basin and its implications to phytoremediation

Abstract: Examination of a former industrial sludge basin containing organic pollutants showed that the basin had undergone substantial ecological recovery through natural forces following the removal of surface water in 1982. Conventional phases of ecological recovery (plant invasion and succession) have occurred, but the structure of the biodiverse plant community (51 species and 22 families) was different from that at a recovering non-polluted disturbed site. Three plant species (Bermuda grass, mulberry, and sunflowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Forty quadrants (1 m  1 m) were placed randomly on each slope. The plant coverage was measured using the method by Olson and Fletcher (2000). The Margalef index R and ShannonWiener diversity index H 0 were calculated to characterize plant richness and plant diversity, respectively.…”
Section: Plant Coverage and Plant Diversitymentioning
confidence: 99%
“…Forty quadrants (1 m  1 m) were placed randomly on each slope. The plant coverage was measured using the method by Olson and Fletcher (2000). The Margalef index R and ShannonWiener diversity index H 0 were calculated to characterize plant richness and plant diversity, respectively.…”
Section: Plant Coverage and Plant Diversitymentioning
confidence: 99%
“…Italian ryegrass, sorghum, maize and alfalfa are recognized as phytoremediators (Radwan et al, 1995;Wiltse et al, 1998;Pradhan et al, 1999;Châineau et al, 2000;Banks et al, 2003b;Parrish et al, 2004). Bermuda grass, sunflower, southern crabgrass and red clover are recognized as hydrocarbon-tolerant plants (Adam and Duncan, 1999;Olson and Fletcher, 2000). These studies suggested that grass species and Leguminosae could be suitable for phytoremediation of petroleum hydrocarbon-contaminated soil.…”
mentioning
confidence: 99%
“…An ecological study of this recovering site (Olson and Fletcher 2000) showed that it differs markedly from the recovery pattern and plant diversity at a nearby site that had simply had soil dumped on it. Three plant species, mulberry, sunflower (Helianthus annuus), and Bermuda grass (Cynodon dactylon), were predominant at the sludge basin, while a much wider range of species was important at the other disturbed site.…”
Section: Ecological Observations On Choice Of Plants For Phytoremmentioning
confidence: 97%